2021
DOI: 10.1021/acs.jproteome.0c00905
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Intrinsic Cardiorespiratory Fitness and Serum and Skeletal Muscle Metabolomics Profile

Abstract: Intrinsic cardiorespiratory fitness (iCRF) indicates the CRF level in the sedentary state. However, even among sedentary individuals, a wide interindividual variability is observed in the iCRF levels, whose associated molecular characteristics are little understood. This study aimed to investigate whether serum and skeletal muscle metabolomics profiles are associated with iCRF, measured by maximal power output (MPO). Seventy sedentary young adults were submitted to venous blood sampling, a biopsy of the vastus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…While the tricarboxylic acid (TCA) cycle intermediate citric acid only showed a relevant positive correlation with the VO 2peak in females, malic acid and succinic acid tended to be positively linked to CRF in both sexes. Previous studies revealed a rise in fasting plasma malic acid after weight loss and PE intervention in obese women [ 58 ], a training-induced increase in muscular succinic acid in subjects at risk of metabolic disease [ 52 ], or a slightly positive correlation between CRF and serum succinic acid in healthy young men [ 59 ]. Despite weak bivariate correlations, our results support the suggestion that specific TCA cycle intermediates might be potentially interesting blood markers of the beneficial effects of chronic PA occurring at a muscular level, such as an increased mitochondrial density or TCA cycle capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the tricarboxylic acid (TCA) cycle intermediate citric acid only showed a relevant positive correlation with the VO 2peak in females, malic acid and succinic acid tended to be positively linked to CRF in both sexes. Previous studies revealed a rise in fasting plasma malic acid after weight loss and PE intervention in obese women [ 58 ], a training-induced increase in muscular succinic acid in subjects at risk of metabolic disease [ 52 ], or a slightly positive correlation between CRF and serum succinic acid in healthy young men [ 59 ]. Despite weak bivariate correlations, our results support the suggestion that specific TCA cycle intermediates might be potentially interesting blood markers of the beneficial effects of chronic PA occurring at a muscular level, such as an increased mitochondrial density or TCA cycle capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Choline participates in multiple pathways of lipid or AA metabolism, serving as a precursor for PC species, the neurotransmitter acetylcholine, or betaine. Circulating choline can result from diet or PC breakdown [ 61 ] and was shown to be either lower [ 18 ] or higher [ 59 , 62 ] in fitter individuals. Even though a more efficient conversion of PCs to choline in trained individuals was assumed [ 62 ], it cannot be excluded that female KarMeN subjects with high CRF were also characterized by a higher dietary choline intake.…”
Section: Discussionmentioning
confidence: 99%
“…A total of eighty healthy and sedentary young Caucasian men, which seventy were defined as completers [age: 23.7 ± 3.0 yr; height: 1.74 ± 0.06 m; body mass: 75.2 ± 8.8; body fat: 20.0 ± 7.4%; body mass index (BMI): 24.8 ± 2.5 kg·m −2 ], from the TIMES study, were used for analysis (Castro A., et al, 2019 ). Briefly, participants were sedentary and did not engage in regular exercise defined as 30 min.wk −1 at an energy expenditure of 6 METS or more in the previous 4 months (Riebe et al, 2018 ; Castro A., et al, 2019 ; Castro et al, 2021 ). All participants were free from diabetes (fasting glucose > 7.0 mmol·L−1), hypertension (blood pressure > 140/90 mmHg), dyslipidemia (based on medication use), severe obesity (defined as body mass index > 33 kg·m −2 ), smoking, metabolic disorders, heart diseases, musculoskeletal problems interfering with exercise or significant chronic respiratory conditions (Castro A., et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…MPO was estimated as W+[25·( t /60)], where W is the last load reached and t is the number of seconds in the test's final load (Kuipers et al, 1985 ). The highest MPO value recorded between tests was considered for the analyses and defined as the measure of CRF (Castro A., et al, 2019 ; Castro et al, 2021 ). The within-test coefficient of variations (CV) and intraclass correlation coefficient (ICC) were 2.8% and 0.98, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation